Personalized Learning in a Digital Environment - Surur, Agus Miftakus; Ulfa, Saida; Soepriyanto , Yerry; Hasnah Binti , Mohamed (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Utilizing advanced learning technologies, such as data analysis and artificial intelligence, teachers can identify student learning patterns, anticipate possible difficulties, and provide specific additional support. For example, by analyzing students' engagement with online learning platforms, teachers can tailor interventions to address individual learning needs, leading to more effective learning outcomes. Moreover, personalized learning in a digital environment goes beyond the delivery of content; it involves fostering 21st century skills such as critical thinking, communication, collaboration, innovation, and problem-solving. Research has shown that integrating technology into project-based learning activities can significantly enhance students' ability to develop these skills. By optimizing the potential of personalized learning approaches in a digital environment, educators can ensure that every student has an equal opportunity to develop the skills necessary to thrive in an ever-changing world.